Methodology of Organizing Geographical Areas and Using Them - Olimova Aziza Abdullaevna (Academia One Publishing, 2023)
The article describes the practical importance of geographic sites, the method of organizing observation and practical work in geography classes.
Keywords: geographical area; experimental lesson